2019
DOI: 10.3390/antiox8090391
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Corn Starch Bio-Active Edible Packaging Films Based on Zein Incorporated with Orange-Peel Oil

Abstract: Zein, corn starch (CS), and orange-peel oil (OPO) extracted from orange peels were used to prepare novel corn starch/orange-peel oil/zein nanocapsules (OZN) bio-active food packaging materials. The results showed that the OZN were round, smooth and in compact morphology with an average diameter of 102.7 ± 10.5 nm from OPO and zein (3:10, w/w). By testing the turbidity and atomic force microscopy (AFM) of OZN and the mechanical properties and water vapor permeability of the composite films, the comprehensive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 59 publications
(62 reference statements)
2
13
0
Order By: Relevance
“…A similar trend of L* values was also obtained when the different concentrations of Thymus kotschyanus essential oil were added into starch/chitosan composite films [ 21 ]. Furthermore, Wang et al [ 22 ] reported that both neat CS film and CS film incorporated with orange-peel oil and zein nanocapsules exhibited high L* values, consistent with the findings in this work.…”
Section: Resultssupporting
confidence: 92%
“…A similar trend of L* values was also obtained when the different concentrations of Thymus kotschyanus essential oil were added into starch/chitosan composite films [ 21 ]. Furthermore, Wang et al [ 22 ] reported that both neat CS film and CS film incorporated with orange-peel oil and zein nanocapsules exhibited high L* values, consistent with the findings in this work.…”
Section: Resultssupporting
confidence: 92%
“…Only three of these compounds showed moderate DPPH scavenging activity and lipid peroxidation inhibitory activities with IC50 values ranging from 34.7 to 89.1 µM [48]. Regarding starch-based films, it was shown that the incorporation of orange peel oil/zein nanocapsules provided DPPH radical scavenging activity of 30% [49]. Yun at al.…”
Section: Antioxidant Capacitymentioning
confidence: 98%
“…Orange peel oil/zein microcapsules (11 wt%) Wang, Zhang, Ahmed, Qin, & Liu, 2019) Orange peel oil/zein microcapsules (43 wt%)…”
Section: Ta B L Ementioning
confidence: 99%